Les SCOP d’architecture : un modèle de coopération ? - Fanny Delaunay; Estelle Gourvennec (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
In the field of urban fabric, the recurrent use of the terms “collaboration”, “cooperation” or “participation” attests to a new injunction of “co” models. Referring to the idea of doing things together, the concrete variations between them remain unclear. This article proposes to shed some light on a subdivision of architectural firms that have chosen to operate under the cooperative model. The analysis of the ideals specific to the structure of cooperative and participative agencies (SCOP), along with the scenes that express their specificity will reveal what “collaboration” entails in the life of an agency.